MANAJEMEN STRATEGIS PADA ORGANISASI NON PROFIT (ONP) - Muallief Umar (LP2M STAI Miftahul 'Ula (STAIM) Nganjuk, 2021)
This article intends to conduct counter discourse by focusing on the discussion of the implementation of strategic management in ONP as a